Wind and Trees: Lessons Learned from Hurricanes - Mary L. Duryea; Eliana Kampf (EDIS, 2007)
FOR-118, a 17-page full-color fact sheet by Mary L. Duryea and Eliana Kampf, is part of the Urban Forest Hurricane Recovery Program series. It reports on the lessons learned from research conducted after 10 hurricanes by scientists at the University of Florida/IFAS, providing many recommendations for homeowners and communities. Includes references. Published by the UF School of Forest Resources and Conservation, September 2007.